2022
DOI: 10.3389/fmed.2022.864570
|View full text |Cite
|
Sign up to set email alerts
|

Potential Blood DNA Methylation Biomarker Genes for Diagnosis of Liver Fibrosis in Patients With Biopsy-Proven Non-alcoholic Fatty Liver Disease

Abstract: Background and objectiveThis pilot study aimed to identify potential blood DNA methylation (BDM) biomarker genes for the diagnosis of liver fibrosis in non-alcoholic fatty liver disease (NAFLD).MethodsWe included a total of 16 NAFLD patients with significant (SLF, liver fibrosis stage ≥ 2) and 16 patients with non-significant liver fibrosis (NSLF, fibrosis stages 0–1). The association between BDM and liver fibrosis was analyzed. Genes were selected based on a stepwise-filtering with CpG islands containing sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…They can also cause non-genomic signaling through activating the PI3K/AKT or MAPK/ERK pathways, resulting in the expression of target genes related to inflammatory pathways, IR, and lipid accumulation [ 4 , 34 , 37 ]. Regarding epigenetic alterations, EDCs can regulate gene expression of proteins involved in DNA methylation and histone modifications [ 38 , 44 , 45 ]. In addition, EDC exposure is also linked to miRNA regulation, leading to dysfunction of related pathways, causing liver damage, and disrupting liver homeostasis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can also cause non-genomic signaling through activating the PI3K/AKT or MAPK/ERK pathways, resulting in the expression of target genes related to inflammatory pathways, IR, and lipid accumulation [ 4 , 34 , 37 ]. Regarding epigenetic alterations, EDCs can regulate gene expression of proteins involved in DNA methylation and histone modifications [ 38 , 44 , 45 ]. In addition, EDC exposure is also linked to miRNA regulation, leading to dysfunction of related pathways, causing liver damage, and disrupting liver homeostasis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, DNA methylation is the most frequently studied epigenetic regulation resulting from EDCs [ 38 ]. It has been proposed that DNA methylation could stratify medium-to-severe MASLD fibrosis and be used as a valuable non-invasive tool in the future [ 44 , 45 ]. The main proteins that participate in DNA and histone methylation are the histone methyltransferase and the DNA methyltransferase (DNMT) [ 46 ].…”
Section: Edcs and Developmental Origins Of Masldmentioning
confidence: 99%
“…Nucleotide methylation markers have the potential as therapeutic targets and staging biomarkers. They are expected to identify patients with early and progressive MAFLD by developing noninvasive operational screening techniques, such as blood-derived biomarkers ( 182 ). Because the nucleotide methylation or demethylation state is reversible, a shift from an HFD to a regular diet and weight loss after bariatric surgery can also partially normalize the DNA methylation profile in MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that blood DNA methylation markers may differentiate NAFLD patients with nonsignificant liver fibrosis from those with significant fibrosis [ 52 ]. Several genes have been identified as potential blood methylation biomarkers for the diagnosis of liver fibrosis in NAFLD, including CISTR, IFT140, and RGS14 [ 52 ].…”
Section: Dna Methylationmentioning
confidence: 99%